WHAT ARE THE IMPORTANT FACTORS TO IMPROVING ECONOMIC PERFORMANCE? EVIDENCE FORM MANUFACTURING INDUSTRY - Arry Eksandy; Irma Paramita Sofia (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
The purpose of this study is to determine the influence of tangible assets, supply chain management, and superior performance on economic performance in manufacturing companies in Indonesia. The research time period used is 3 years, namely the period 2016-2018. The sampling technique uses purposive sampling technique. Based on the established criteria obtained 33 companies. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. The analysis method used is panel data regression analysis. The results showed that superior performance has a significant positive effect on economic performance. Tangible assets and supply chain management have no effect on economic performance.